Application of food thickener in prevention of stroke-associated pneumonia and relief of dysphagia (食品增稠剂预防卒中相关性肺炎及改善吞咽困难的临床观察) - WU Min (吴敏) (Association of Integrative Nursing, 2021)
Objective To observe the effect of diet intervention with food thickener in prevention of stroke-associated pneumonia (SAP) and relief of dysphagia. Methods Totally 180 patients with dysphagia after stroke were randomly divided into the observation group and control group, with 90 cases in each group. All patients received routine care and rehabilitation training, and those in the observation group were given systematic diet intervention with food thickener. The incidences of SAP and aspiration were observed, and the recovery of swallowing function was evaluated by Water Swallow Test. Results The incidence of aspiration in the observation group was lower than that in the control group (P＜0. 05). The incidence of dysphagia in the observation group was lower than that in the control group (P＜0. 05). There was no significant difference in rate of swallowing function recovery between two groups (P＜0. 05). Conclusion The diet intervention with food thickener is effective to reduce the risk of aspiration, showing a positive role in prevention of SAP. (目的 观察食品增稠剂预防卒中相关性肺炎及改善吞咽困难的临床效果。方法 将180例脑卒中吞咽困难患者随机分为观察组和对照组, 各90例。对照组给予常规护理和康复训练, 观察组在常规护理的基础上行系统性食品增稠剂饮食训练。干预后观察并记录患者卒中相关性肺炎的发生情况, 根据洼田饮水试验对患者吞咽障碍恢复效果进行评价。结果 观察组患者误吸发生率低于对照组, 差异有统计学意义(P＜0. 05); 观察14 d后, 观察组卒中相关性肺炎发生率低于对照组, 差异有统计学意义(P＜0. 05)。两组吞咽功能好转率比较, 差异无统计学意义(P＞0. 05)。结论 通过食品增稠剂的应用可以明显减少呛咳、噎食的发生, 从而降低误吸的发生风险, 对卒中相关性肺炎起到积极的预防效果。)